THE EFFICIENCY OF MANUFACTURING TRADE BETWEEN TURKEY AND THE EUROPEAN UNION - DEMİR, Memduh Alper; BİLİK, Mustafa; UTKULU, Utku (ACC Publishing, 2019)
In this study, the manufacturing trade efficiency of Turkey with the European Union-25 (EU-25) is examined by applying stochastic frontier gravity model over the period of 2006–2016. In addition, this study is analyzed whether there is a convergence in efficiency of manufacturing trade between Turkey and the EU-25. Findings show that Turkey’s average trade efficiency score is 56,3% and it ranged from 0,01% to 92,5% for all countries. Manufacturing trade flow of Turkey is significantly affected by income, market size of the trading partner and the distance between them. The findings also suggest that trade flows are affected by the global financial crisis.
Keywords: 8. Economic growth; 16. Peace & justice; 7. Clean energy